Severe Antithrombin III Deficiency in an Infant Associated with Multiple Arterial and Venous Thromboses - Mendelsohn, Geoffrey; Gomperts, Edward D.; Gurwitz, Dennis (Thrombosis and Haemostasis, 1976)
Inherited antithrombin III (AT-II, heparin cofactor) deficiency is a rare condition, presenting with thrombotic disease in adult life. This paper reports an 8 months old South African Black male infant with multiple large vessel venous and arterial thromboses, and E. coli septicaemia. This was associated with an extremely low plasma AT-II level. Micronodular cirrhosis and intracytoplasmic hyaline globules in the liver cells were present. These globules were eosinophilic, and PAS-positive after diastase. They measured approximately 5 μ to 30 μ in diameter, occurred singly in the liver cells and were located mainly in the periportal areas. The histological findings in the liver are similar to those observed in α1-antitrypsin (AAT) deficiency in which the intracytoplasmic globules represent accumulation of altered AAT. Immunochemical studies carried out on formalin fixed tissue failed to detect cross reaction material with anti-α1 antitrypsin or anti-AT III antiserum. This is the first case report of AT-III deficiency presenting in infancy. It is also the first case associated with distinctive liver pathology.The available data presented are insufficient to distinguish between an inborn defect and acquired causes of the severely depressed AT-III plasma level and the distinctive liver pathology.